Enabling macroscopic superlubricity in TaC/a-C nanocomposite film by atomic-level Au. (15th April 2023) - Zhang, Yu; He, Xingjia; Liu, Manman; Zhang, Kan; Singh, David J.; Fan, Xiaofeng; Wen, Mao; Zheng, Weitao
Abstract: Endowing the hard protective coating systems with macroscopic superlubricity can adequately minimize unnecessary material consumption and energy waste caused by friction and wear. Herein, a novel scheme for realizing superlubricity-protective bifunction is demonstrated, namely introducing atomic-level dispersed Au atoms (∼1.4 at.%) into the TaC / amorphous carbon (a-C) nanocomposite structure consisting of the TaC-nanoparticles-based network backbone and the a-C filler. With the aid of the atomic-level dispersed Au atoms reducing the ordered transformation barrier of a-C, the in-situ formation of graphite-like carbon (GLC) flakes during the sliding process wrap the TaC grains to form TaC@GLC nanoscrolls in the shearing layer for multi-contact configuration and incommensurate contact, thereby obtaining the robust macroscopic superlubrication with the friction of coefficient of ∼0.002 and the ultra-low wear rate of ∼8.80 × 10 −10 (mm −3 /Nm). This strategy of triggering in-situ self-assembled nanoscrolls from hard protective coatings provides a new avenue to enable macroscopic superlubricity for robust engineering applications. Graphical abstract: Image, graphical abstract